Christian education : a guide to the foundations of ministry - Cardoza, Freddy (Grand Rapids, MI, Baker Academic, 2019)
This introductory textbook solidly situates Christian education in the church and ministry context of the 21st century. With over 20 years of ministry, teaching, and leadership experience, Freddy Cardoza is uniquely qualified to bring together a wide range of Christian educators. This volume features the expertise of 25 evangelical scholars of Christian education, including diverse, next-generation voices in the field. It provides balanced biblical-theological and practical perspectives for church and parachurch leaders, equipping them to meet the ever-changing needs of our world. --
Includes bibliographical references and index
Keywords: Education (Christian theology); Christian education